2021
DOI: 10.1101/gad.344473.120
|View full text |Cite
|
Sign up to set email alerts
|

TFs for TEs: the transcription factor repertoire of mammalian transposable elements

Abstract: Transposable elements (TEs) are genetic elements capable of changing position within the genome. Although their mobilization can constitute a threat to genome integrity, nearly half of modern mammalian genomes are composed of remnants of TE insertions. The first critical step for a successful transposition cycle is the generation of a full-length transcript. TEs have evolved cis-regulatory elements enabling them to recruit host-encoded factors driving their own, selfish transcription. TEs are generally transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 157 publications
(251 reference statements)
1
67
0
Order By: Relevance
“…SINEs are known to exploit the LINE retrotransposition machinery for mobilization, often facilitated by 3′ end sequence similarity between LINE and SINE partners [ 31 , 32 ]. Although LTR and LINE retrotransposons are transcribed by the RNA polymerase II machinery, assisted by a few sequence-specific transcription factors (TFs), most SINEs are transcribed by RNA polymerase III due to the presence of internal control regions (A box and B box) recognized by the Pol III-specific basal transcription factor TFIIIC [ 33 , 34 ]. Indeed, the evolutionary origin of most SINEs has been traced back to Pol III-transcribed genes coding for abundant small RNAs, such as tRNA, 5S rRNA and 7SL RNA, all employing TFIIIC as a sequence-specific DNA binding protein essential for transcription complex assembly [ 35 ].…”
Section: Retrotransposons and Their Impact On Mammalian Genome Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…SINEs are known to exploit the LINE retrotransposition machinery for mobilization, often facilitated by 3′ end sequence similarity between LINE and SINE partners [ 31 , 32 ]. Although LTR and LINE retrotransposons are transcribed by the RNA polymerase II machinery, assisted by a few sequence-specific transcription factors (TFs), most SINEs are transcribed by RNA polymerase III due to the presence of internal control regions (A box and B box) recognized by the Pol III-specific basal transcription factor TFIIIC [ 33 , 34 ]. Indeed, the evolutionary origin of most SINEs has been traced back to Pol III-transcribed genes coding for abundant small RNAs, such as tRNA, 5S rRNA and 7SL RNA, all employing TFIIIC as a sequence-specific DNA binding protein essential for transcription complex assembly [ 35 ].…”
Section: Retrotransposons and Their Impact On Mammalian Genome Evolutionmentioning
confidence: 99%
“…First of all, many binding sites for diverse TFs are contributed by retrotransposons, as mainly revealed by genome-wide TF occupancy mapping by chromatin immunoprecipitation coupled with high throughput sequencing (ChIP-seq) [ 106 ]. Although some of the TF binding sites carried by TEs are justified by their need to employ host TFs for their own life cycle, others may have been acquired independently through TE propagation mechanisms [ 34 ]. Molecular evolution studies have revealed waves of expansion of the TF target repertoire over the course of vertebrate evolution, with TEs majorly contributing to such expansions [ 107 ].…”
Section: Retrotransposons and Their Impact On Mammalian Genome Evolutionmentioning
confidence: 99%
“…Murine ESCs (mESCs) in the pluripotent state exhibit relatively permissive chromatin, with many accessible regions which are thought to comprise active mESC enhancers but also primed enhancers that can be activated at later stages during differentiation (Buecker et al ., 2014; Wu et al ., 2016). The expression of genes in mESCs is also controlled by transposable elements, for example from the ERVK family, that can act as enhancers that control the expression of associated genes (Sundaram et al ., 2017; Todd et al ., 2019; Hermant and Torres-Padilla, 2021). The pluripotency of mESCs and their ability to self-renew critically depend on the actions of specific TFs including OCT4 and SOX2, NANOG, KLF4, and ESRRB (Chambers and Tomlinson, 2009; Young, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…TEs are reservoirs of functional transcription factor binding sites. Since these sequence are widespread in the genome, they are largely contributing to the innovation of regulatory networks in a tissue-specific fashion (Chuong et al, 2017; Sundaram and Wang, 2018; Hermant and Torres-Padilla, 2021). Although LTR dominate this relationship, search for binding motifs in young L1 in human and mouse has revealed the presence of various TF motifs, including CTCF, YY1 and MYC (Sun et al, 2018; Sundaram and Wang, 2018).…”
Section: Discussionmentioning
confidence: 99%